Effects Of Aging Condition, Preconditioned Temperature And Anti-Stripping Agent On The Adhesive And Cohesive Behaviour Of Asphalt Binder And Mastics - Goh, Xiao Wen (Universiti Sains Malaysia, 2017)
Warm Mix Asphalt (WMA) has gain wide acceptance by asphalt industry especially in the United States due to its ability to lower asphalt mixing and compaction temperatures by 20°C to 55°C compared to the conventional Hot Mix Asphalt (HMA). This characteristic makes WMA a greener technology as less emission will be released into the air. However, the lowered temperature gives rise to greater moisture susceptibility, which related to coating and bonding problems. Addition of anti-stripping agents is a feasible solution to the current predicament. The two anti-stripping agents used were ZycoTherm and Tough Fix. The impact test was conducted, using a newly fabricated mould, and the effects of aging conditions and preconditioning temperatures of bitumen incorporating either ZycoTherm or Tough Fix, were investigated. The analysis results showed that bond strength of binder and mastics was at their strongest at intermediate temperature (35°C) and it improved directly proportional to the aging condition. The overall test results indicated that both ZycoTherm and Tough Fix had significant effects on improving the performance of bitumen in terms of bond strength and fracture toughness. Image analysis technique was used to classify the adhesive and cohesive failures of bitumen after undergoing impact test. It was found that percentage adhesive failure of bitumen increases at aged condition and low temperature.